FRI0102 SERUM TNFΑ LEVELS AT 24 HOURS AFTER FIRST ADMINISTRATION OF CERTOLIZUMAB PEGOL PREDICT EFFECTIVENESS AT WEEK 12 IN PATIENTS WITH RHEUMATOID ARTHRITIS FROM TSUBAME STUDY (UMIN ID:0002381). (2nd June 2020) - Miyazaki, Y.; Nakano, K.; Nakayamada, S.; Kubo, S.; Iwata, S.; Hanami, K.; Fukuyo, S.; Miyagawa, I.; Yamaguchi, A.; Kawabe, A.; Kazuyoshi, S.; Tanaka, Y.
Abstract : Background: To increase the remission rate of rheumatoid arthritis (RA), it is necessary to determine the efficacy of the tumor necrosis factor (TNF) inhibitor as early as possible. Moreover, the response to certolizumab pegol (CZP) at 12 weeks has been reported to predict its long-term efficacy. Objectives: As part of a prospective single-center observational study (TSUBAME study), we prospectively enrolled patients to be treated with CZP in our institution to evaluate its effectiveness and safety starting at 24 hours after the first dose in clinical settings, while recording blood CZP concentrations and biomarkers over time to examine their correlation with clinical effects. Methods: One hundred patients with RA and inadequate response to MTX who received CZP were enrolled in the TSUBAME study. The changes in serum TNFα, IL-6, and CZP levels at 24 hours after first administration of CZP were measured, and the correlation between serum biomarkers and clinical response was determined. Results: At 24 hours after CZP initiation, significant improvement was observed in the disease activity (baseline and 24 h: 5.4 ± 1.3, 5.0 ± 1.3, respectively, p < 0.01), which was maintained until week 12. (baseline and 12 w: 5.4 ± 1.3, 3.3 ± 1.4, respectively, p < 0.01). Serum TNFα and IL-6 levels significantly decreased at 24 hours after first administration of CZP compared to baseline. No correlation was found between TNFα and IL-6 levels at baseline and the clinical response. According to univariate analysis, low serum TNFα and IL-6 levels and high CZP levels at 24 hours were associated with DAS28 (ESR) remission at 12 weeks. According to multivariate analysis, low serum TNFα levels at 24 hours were significantly associated with DAS28 (ESR) remission at 12 weeks (OR 0.05, 95%CI 0.01, 0.75, p = 0.03). Based on these findings, an ROC curve was created using remission according to the DAS28 (ESR) at week 12 as a dependent variable and TNFα concentration at 24 hours as an independent variable, resulting in a cut-off value of 0.76 pg/ml. From this result, the TNFα concentration at 24 hours was divided into 2 groups according to this cut-off, and the rates of remission according to the DAS28 (ESR) at week 12 were compared. In the group with TNFα concentration at 24 hours below the cut-off value, the rate of remission according to the DAS28 (ESR) at week 12 was significantly higher than in the group with TNFα concentration at 24 hours above the cut-off value (below the cut-off: above the cut-off = 56.3%: 21.6%, p < 0.001). Between the group that achieved remission according to the DAS28(ESR) and the group that did not achieve remission at week 12, there was almost no difference in the distribution of TNFα concentrations at baseline; however, the distribution of TNFα concentrations at 24 hours was lower in the group that achieved remission. Conclusion: CZP was effective where serum TNFα was strongly neutralized within 24 hours. These results suggest that low serum TNFα levels at 24 hours after first administration of CZP may predict the effectiveness of CZP. To increase the remission rate in RA, it is necessary to determine the effectiveness of the molecular targeted drugs used at an early point, in addition to how rapid the onset of action is. CZP is extremely fast-acting, and its effectiveness can be predicted as early as 24 hours after the first dose, suggesting that it may be possible to determine the effectiveness early. Acknowledgments: The authors thank Ms. M. Hirahara for providing excellent technical assistance. Disclosure of Interests: Yusuke Miyazaki Grant/research support from: Astellas Pharma Inc and UCB S.A., Kazuhisa Nakano: None declared, Shingo Nakayamada Grant/research support from: Mitsubishi-Tanabe, Takeda, Novartis and MSD, Speakers bureau: Bristol-Myers, Sanofi, Abbvie, Eisai, Eli Lilly, Chugai, Asahi-kasei and Pfizer, Satoshi Kubo: None declared, Shigeru Iwata: None declared, Kentaro Hanami: None declared, Shunsuke Fukuyo: None declared, Ippei Miyagawa: None declared, Ayako Yamaguchi: None declared, Akio Kawabe: None declared, SAITO KAZUYOSHI: None declared, Yoshiya Tanaka Grant/research support from: Asahi-kasei, Astellas, Mitsubishi-Tanabe, Chugai, Takeda, Sanofi, Bristol-Myers, UCB, Daiichi-Sankyo, Eisai, Pfizer, and Ono, Consultant of: Abbvie, Astellas, Bristol-Myers Squibb, Eli Lilly, Pfizer, Speakers bureau: Daiichi-Sankyo, Astellas, Chugai, Eli Lilly, Pfizer, AbbVie, YL Biologics, Bristol-Myers, Takeda, Mitsubishi-Tanabe, Novartis, Eisai, Janssen, Sanofi, UCB, and Teijin